Discovery of a Novel Cellobiose Dehydrogenase from Cellulomonas palmilytica EW123 and Its Sugar Acids Production - Ake-kavitch Siriatcharanon; Sawannee Sutheeworapong; Sirilak Baramee; Rattiya Waeonukul; Patthra Pason; Akihiko Kosugi; Ayaka Uke; Khanok Ratanakhanokchai; Chakrit Tachaapaikoon (Journal of microbiology and biotechnology, 2024)
Cellobiose dehydrogenases (CDHs) are a group of enzymes belonging to the hemoflavoenzyme group, which are mostly found in fungi. They play an important role in the production of acid sugar. In this research, CDH annotated from the actinobacterium Cellulomonas palmilytica EW123 (CpCDH) was cloned and characterized. The CpCDH exhibited a domain architecture resembling class-I CDH found in Basidiomycota. The cytochrome c and flavin-containing dehydrogenase domains in CpCDH showed an extra-long evolutionary distance compared to fungal CDH. The amino acid sequence of CpCDH revealed conservative catalytic amino acids and a distinct flavin adenine dinucleotide region specific to CDH, setting it apart from closely related sequences. The physicochemical properties of CpCDH displayed optimal pH conditions similar to those of CDHs but differed in terms of optimal temperature. The CpCDH displayed excellent enzymatic activity at low temperatures (below 30℃), unlike other CDHs. Moreover, CpCDH showed the highest substrate specificity for disaccharides such as cellobiose and lactose, which contain a glucose molecule at the non-reducing end. The catalytic efficiency of CpCDH for cellobiose and lactose were 2.05 x 10 5 and 9.06 x 10 4 (M -1 s -1 ), respectively. The result from the Fourier-transform infrared spectroscopy (FT-IR) spectra confirmed the presence of cellobionic and lactobionic acids as the oxidative products of CpCDH. This study establishes CpCDH as a novel and attractive bacterial CDH, representing the first report of its kind in the Cellulomonas genus.